Advancing urban water security: The urbanization of water–society relations and entry–points for political engagement. Issue 6 (18th August 2021) - Empinotti, Vanessa Lucena; Budds, Jessica; Jepson, Wendy; Millington, Nate; Nicolau Ferrara, Luciana; Geere, Jo-Anne; Grandisoli, Edson; Gutierres Arteiro Da Paz, Mariana; Peregrina Puga, Bruno; Macedo Alves, Estela; Cawood, Sally; Jacobi, Pedro Roberto; et al.
ABSTRACT: We seek to advance a critical and relational concept of urban water security that theorizes urban processes in relation to the hydro-social dynamics that produce experiences of water securities and insecurities at multiple scales. Our intention is to set out an analytical framework that both examines the social relations that underpin water insecurity and goes beyond the urban as merely the context in which water provision and risk take place. We seek to mobilize this concept to envision meaningful water policies and hydro-social practices to enhance social equity and empowerment for urban communities.